A novel humanized mouse model of Huntington disease for preclinical development of therapeutics targeting mutant huntingtin alleles. (19th January 2017) - Southwell, Amber L.; Skotte, Niels H.; Villanueva, Erika B.; Østergaard, Michael E.; Gu, Xiaofeng; Kordasiewicz, Holly B.; Kay, Chris; Cheung, Daphne; Xie, Yuanyun; Waltl, Sabine; Dal Cengio, Louisa; Findlay-Black, Hailey; et al.
Abstract: Huntington disease (HD) is a neurodegenerative disease caused by a mutation in the huntingtin ( HTT ) gene. HTT is a large protein, interacts with many partners and is involved in many cellular pathways, which are perturbed in HD. Therapies targeting HTT directly are likely to provide the most global benefit. Thus there is a need for preclinical models of HD recapitulating human HTT genetics. We previously generated a humanized mouse model of HD, Hu97/18, by intercrossing BACHD and YAC18 mice with knockout of the endogenous mouse HD homolog ( Hdh ). Hu97/18 mice recapitulate the genetics of HD, having two full-length, genomic human HTT transgenes heterozygous for the HD mutation and polymorphisms associated with HD in populations of Caucasian descent. We have now generated a companion model, Hu128/21, by intercrossing YAC128 and BAC21 mice on the Hdh −/− background. Hu128/21 mice have two full-length, genomic human HTT transgenes heterozygous for the HD mutation and polymorphisms associated with HD in populations of East Asian descent and in a minority of patients from other ethnic groups. Hu128/21 mice display a wide variety of HD-like phenotypes that are similar to YAC128 mice. Additionally, both transgenes in Hu128/21 mice match the human HTT exon 1 reference sequence. Conversely, the BACHD transgene carries a floxed, synthetic exon 1 sequence. Hu128/21 mice will be useful for investigations of human HTT that cannot be addressed in Hu97/18 mice, for developing therapies targeted to exon 1, and for preclinical screening of personalized HTT lowering therapies in HD patients of East Asian descent.